2012
DOI: 10.1038/nm.2866
|View full text |Cite
|
Sign up to set email alerts
|

Large intestine–targeted, nanoparticle-releasing oral vaccine to control genitorectal viral infection

Abstract: Both rectal and vaginal mucosal surfaces serve as transmission routes for pathogenic microorganisms. Vaccination through large intestinal mucosa, previously proven protective for both mucosal sites in animal studies, can be achieved successfully by direct intra-colorectal (i.c.r.) administration, which is, however, clinically impractical. Oral delivery seems preferable, but risks vaccine destruction in the upper gastrointestinal tract. Therefore, we designed a large intestine-targeted oral delivery with pH-dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
138
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(143 citation statements)
references
References 32 publications
5
138
0
Order By: Relevance
“…24 These findings demonstrate the potential for nanoparticle-based oral drug delivery. 227,228 However, nanoparticles retained in the gastrointestinal tract may affect adversely its structure and function. For example, chitosan nanoparticles penetrated the mucus and epithelial cell layer and disrupted the tight junctions of the epithelial layer.…”
Section: Digestive Nanotoxicitymentioning
confidence: 99%
“…24 These findings demonstrate the potential for nanoparticle-based oral drug delivery. 227,228 However, nanoparticles retained in the gastrointestinal tract may affect adversely its structure and function. For example, chitosan nanoparticles penetrated the mucus and epithelial cell layer and disrupted the tight junctions of the epithelial layer.…”
Section: Digestive Nanotoxicitymentioning
confidence: 99%
“…Fine tuning of the formulation may be necessary to account for longer transit times in the gut, as well as slightly higher pH values (around 7.3) in the distal small intestine. 12 In our previous study, we designed and developed an enzyme/pH dual-sensitive polymeric mixture nanoparticle (NP) system composed of an enzyme-sensitive azo-polyurethane (Azo-pu) and a pH-sensitive methacrylate copolymer (Eudragit S100 [ES]) for targeted drug delivery to the inflamed colon, thereby overcoming the limitations of single-triggered release systems. 13 The prepared NPs remained intact in the stomach, and released a drug in a sustained manner in the ileum (pH .7.0), followed by enzyme-triggered release in the presence of the cecal content of rats with colitis.…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, synthetic polymeric nanoparticles and liposomal nanovesicles offer versatile platform technologies that can induce strong adaptive immune responses while avoiding antivector immunity and toxicity issues [43][44][45]. For example, polymeric particles based on biodegradable and biocompatible poly(lactic-co-glycolic) acid (PLGA) copolymer have been extensively investigated for vaccine delivery applications [46][47][48][49][50]. PLGA particles encapsulating HIV-1 peptide antigens administered via the intranasal route elicited Th1/Th2-balanced cellular immune responses in mucosal surfaces [46], while PLGA particles carrying HIV Env peptides administered via the oral route in mice conferred T-cell-mediated protection against viral infection at the rectal and vaginal mucosa [47].…”
Section: Synthetic Nanoparticles For Presentation Of Hiv-1 Antigensmentioning
confidence: 99%
“…For example, polymeric particles based on biodegradable and biocompatible poly(lactic-co-glycolic) acid (PLGA) copolymer have been extensively investigated for vaccine delivery applications [46][47][48][49][50]. PLGA particles encapsulating HIV-1 peptide antigens administered via the intranasal route elicited Th1/Th2-balanced cellular immune responses in mucosal surfaces [46], while PLGA particles carrying HIV Env peptides administered via the oral route in mice conferred T-cell-mediated protection against viral infection at the rectal and vaginal mucosa [47]. Recently, Kasturi et al have elegantly shown that PLGA nanoparticles co-loaded with TLR4 and TLR7/8 agonists can synergistically improve induction of antigen-specific antibody responses in nonhuman primates (NHPs) via triggering germinal center and plasma cell responses in lymphoid tissues [48]; in a subsequent study, the authors have shown that PLGA particles carrying TLR4 and TLR7/8 agonists admixed with soluble recombinant gp140 SIVmac239 Env and Gag p55 enhanced the magnitude and durability of humoral immune responses (6.5-fold and 4.7-fold higher antibody titers for protein + PLGA particles at weeks 27 and 42, compared with protein vaccine adjuvanted with Alum), and protected NHPs future science group Nanoparticles for HIV vaccination Special Report against repeated low-dose, intravaginal challenges with heterologous SIVsmE660 [49].…”
Section: Synthetic Nanoparticles For Presentation Of Hiv-1 Antigensmentioning
confidence: 99%